Strategic interactions in a one-sector growth model - FESSELMEYER, Eric (Institutional Knowledge at Singapore Management University, 2016)
We study the effect of dynamic and investment externalities in a one-sector growth model. In our model, two agents interact strategically in the utilization of capital for consumption, savings, and investment in technical progress. We consider two types of investment choices: complements and substitutes. For each case, we derive the equilibrium and provide the corresponding stationary distribution. We then compare the equilibrium with the social planner's solution.